ANALISIS LOAD FACTOR PERJALANAN KRL COMMUTER LINE BERDASARKAN TITIK JENUH LINTAS ( STUDI KASUS LINTAS BOGOR – MANGGARAI ): ANALISIS LOAD FACTOR PERJALANAN KRL COMMUTER LINE BERDASARKAN TITIK JENUH LINTAS ( STUDI KASUS LINTAS BOGOR – MANGGARAI ) - Erlangga, Aditya Wahyu; Istiantara, Dedik Tri; Nugroho, Ikhsan (Politeknik Perkeretaapian Indonesia Madiun, 2020)
Regions which have the highest population frequency in Indonesia, are Jabodetabek where traffic jams occured almost everyday. PT Kereta Commuter Indonesia has the main duty to provide KRL trips around Jakarta, Bogor, Depok, Tangerang, Bekasi, Cikarang, Maja, and Rangkasbitung. One of the most crowded is Bogor – Manggarai crossing because of the large number of workers from Bogor to Jakarta using KRL. KRL on that area are still lack because there are many passengers who could not catch the train on rush hour and it is very crowded inside the KRL.. From the statements it is needed to analyse the load factor of the Manggarai - Bogor crossing KRL trip to accommodate the passengers safely and comfortably. This analysis aimed to determine the load factor and saturation cross point of the Bogor - Manggarai KRL. The analysis carried out was expected to get the right results to predict when the saturation cross point of the Bogor - Manggarai crossing which could be seen in terms of passenger growth, and obtain the value of load factors based on those calculations. The results of the study stated that when the peak hour trip was now saturated -3.44 years the load factor 153%, the maximum trip based on the initial trip was saturated -1.15 years and the load factor 115%, the stamformation trip 12 showed a saturation rate at 0.58 years and a load a factor of 93%. When off peak hour crossing Bogor - Manggarai trip now showed a saturation rate of 2.71 years and a load factor at 72%, a maximum trip based on an initial trip, showing a 5.1 year rate and a load factor at 53%, a stamformasi 12 trip showing a saturation rate 6.76 years and a load factor at 43%.